2009
DOI: 10.1172/jci39019
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylated PPARα mediates sex-specific gene repression and protects the liver from estrogen-induced toxicity in mice

Abstract: As most metabolic studies are conducted in male animals, understanding the sex specificity of the underlying molecular pathways has been broadly neglected; for example, whether PPARs elicit sex-dependent responses has not been determined. Here we show that in mice, PPARα has broad female-dependent repressive actions on hepatic genes involved in steroid metabolism and immunity. In male mice, this effect was reproduced by the administration of a synthetic PPARα ligand. Using the steroid oxysterol 7α-hydroxylase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
96
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 62 publications
5
96
0
Order By: Relevance
“…Genome-wide microarray transcriptome profiling studies with liver RNA from wild-type and PAR bZip 3KO mice revealed differentially expressed genes involved in xenobiotic detoxification (9) and lipid metabolism (this paper). The latter included Pparα, a gene specifying a nuclear receptor that is well known as a regulator of lipid metabolism, and many PPARα target genes (10) (Fig. S1A).…”
Section: Resultsmentioning
confidence: 99%
“…Genome-wide microarray transcriptome profiling studies with liver RNA from wild-type and PAR bZip 3KO mice revealed differentially expressed genes involved in xenobiotic detoxification (9) and lipid metabolism (this paper). The latter included Pparα, a gene specifying a nuclear receptor that is well known as a regulator of lipid metabolism, and many PPARα target genes (10) (Fig. S1A).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Leuenberger et al (2009) and Montagner et al (2011) compared hepatic mRNA expression profiles between wild-type mice and PPARα-null mice of each sex. The presence of PPARα stimulated a similar number of genes in males and females, but only half of the genes were upregulated by PPARα in common to both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…The liver, the primary target organ of HDBB, is a sexually dimorphic organ (Leuenberger et al, 2009;Montagner et al, 2011). In mammals, more than 1600 hepatic genes are differentially expressed between males and females, and many of them are regulated by differences in pituitary growth hormone secretion, which is pulsatile in males and continuous in females.…”
Section: Discussionmentioning
confidence: 99%
“…Shafaati et al reported that in the SH-SY5Y cell system, CYP7B1 expression was suppressed by HDAC treatment [13]. Subsequently, the study of Leuenberger et al reported that HDAC inhibitor treatment led to an increase in CYP7B1 expression in HepG2 hepatoma cells and that silencing of HDAC1 and HDAC3 activated CYP7B1 in this cell system [51]. Thus while the available evidence is relatively limited, the consistent pattern of results in both the human prostate and mouse liver indicates that both methylation of DNA and/or proteins and histone acetylation are likely to be of importance for the regulation of the expression of CYP7B1.…”
Section: Cyp7b1mentioning
confidence: 99%
“…In an elegant study, Leuenberger et al explored the mechanistic basis for the sexually dimorphic expression and provided evidence that methylation was critical for this to occur [51]. Post 15 translational sumoylation of the peroxisome proliferator-activated receptor-α (Pparα) increases interaction with GA-binding protein (Gabp) and leads to recruitment of HDAC and DNMT, ultimately leading to methylation of CpG residues within a key SP1 site and the trimethylation of lysine 9 of histone H3.…”
Section: Cyp7b1mentioning
confidence: 99%